Oilseed and protein crops grown in French organic farms: an overview of cultivation practices for sunflower and soybean☆ - Le Gall Cécile; Lecomte Vincent; Wagner Dominique (Oilseeds and fats, crops and lipids, 2022)
The development of organic agriculture in France was steady since 2010 but became stronger since 2014. Like other crops, the cultivated areas of organic soybean and sunflower doubled from 2014 to 2018. With a view to better characterize cultural practices in organic production, Terres Inovia and ITAB (in collaboration with Agence Bio) conducted in 2016 and 2017 a national farmers’ survey. These surveys reveal that sunflower was mainly cultivated over the same types of soil than in conventional production but were integrated in more diversified rotations. The main differences between organic and conventional systems concern sowing date and weed control. Organic sunflower was sown very lately compared to conventional one, which impacted the yield severely. Weed were controlled through ploughing, mechanical weeding and crop rotation and weed control was judged as satisfying by a major part of producers. Concerning soybean, a great difference is the use of irrigation which is almost systematic in conventional but concerned only 50% of cultivated area in organic production. Contrary to sunflower, soybean is integrated in short crop rotation, particularly when it was irrigated. This demonstrated the high profitability of soybean in organic systems. Like for sunflower, weed control done through ploughing, mechanical weeding, and crop rotation and weed control was also judged satisfying; nevertheless, criteria on harvest impurities are more severe and to respect them, organic farmers also use hand weeding in complement. These surveys will be reconducted over the years to be able to follow the changes of cultural practices over the years.